La vie en queer : queering sight and envisioning liberated subjectivities - Lim, Kai Tjoon (Nanyang Technological University, 2020)
Sight has hitherto been consistently vilified in theoretical discourse. While feminist and postcolonial theories have succeeded in extending discussions about the gaze within power dynamics, purely naming and uncovering how these visual oppressions function do little to conceptualize possibilities of moving beyond identification processes. Unlike other physical senses such as touch and smell that have already been theorized as bases of ethical intersubjective relationality, sight has yet been reclaimed as part of an affirmative politics to break through normative barriers which undergird the exclusionary processes structuring identity politics. This project is concerned with queer interventions that seek to map a theoretical space for rethinking sight as a possible mode of transgression from the prescriptive molds of identity, and its potential to liberate bodies and constrained subjectivities from the traditional, coercive frameworks of visual objectification.